Consumo de alcohol y su relación con la funcionalidad familiar en los adolescentes de los colegios de la ciudad de Piñas. - Jaramillo Bustamante, Jorge Ricardo (2017)
The present is a descriptive, cross - sectional analytical study accomplished in the from the City of Piñas, Leovigildo Loayza Loayza High School and “Ocho de Noviembre” Educational Unit. With a universe of 2700 students approximately from both schools, it was obtained a sample of 568 students, men and women between 12 and 18 years old, who all agreed to participate in the study, which were chosen at random, according to the number required for the sample. The objective of this project was to establish the relationship between alcohol consumption and family dysfunction, this was established by applying the Alcohol Use Disorders Identification Test (AUDIT) test that values and standardizes alcohol consumption, and the Family Functionality Perception Test (FF-SIL) that values family functionality; 37.15% of the students surveyed consume alcohol and 72,04% of them belong to a dysfunctional family in their various degrees, it is also worth mentioning that about 29.38% of alcohol users fall into categories of drinkers at risk, Harmful or in alcoholic dependence, which also belong to a dysfunctional family which supports the hypothesis suggested in the present study. Therefore it is concluded that family dysfunction is a risk factor for alcohol consumption, since tests of significance such as Chi square, Cramer V and Odds Ratio confirmed the statistical relationship between alcohol consumption and Family dysfunction. Palabras Clave: alcoholism, family dysfunction, adolescents